2015
DOI: 10.1021/acsami.5b03591
|View full text |Cite
|
Sign up to set email alerts
|

Au@Ag Heterogeneous Nanorods as Nanozyme Interfaces with Peroxidase-Like Activity and Their Application for One-Pot Analysis of Glucose at Nearly Neutral pH

Abstract: As substitutes for natural peroxidases, most nanomaterial-based enzyme mimetics (nanozymes) have unique properties such as high stability, low-cost, large surface area, and high catalytic activity. However, they usually work in acidic conditions and thus impede their real applications. In this work, by modulating the nanostructure, composition, and surface property of the bimetallic materials, the positively charged poly(diallyldimethylammonium)-stabilized Au@Ag heterogeneous nanorods (NRs) were developed as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(97 citation statements)
references
References 72 publications
3
94
0
Order By: Relevance
“…Bimetallic nanomaterials consist of two metals and often display enhanced catalytic performance than their monometallic counterparts because of a synergistic effect. Therefore, the peroxidase‐like activity of bimetal nanomaterials such as Au@M (M = Ag, Pt, Bi, Cu), AgM (M = Au, Pd, Pt), and Fe–Co NPs are studied by some groups. The mechanism of peroxidase‐like activity of these metal nanomaterials is that metal nanomaterials can break up the OO bond of H 2 O 2 into two ·OH radical.…”
Section: Peroxidase‐like Activity Of Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bimetallic nanomaterials consist of two metals and often display enhanced catalytic performance than their monometallic counterparts because of a synergistic effect. Therefore, the peroxidase‐like activity of bimetal nanomaterials such as Au@M (M = Ag, Pt, Bi, Cu), AgM (M = Au, Pd, Pt), and Fe–Co NPs are studied by some groups. The mechanism of peroxidase‐like activity of these metal nanomaterials is that metal nanomaterials can break up the OO bond of H 2 O 2 into two ·OH radical.…”
Section: Peroxidase‐like Activity Of Nanomaterialsmentioning
confidence: 99%
“…The application of bimetallic nanomaterials for fabricate colormetric glucose biosensor based on the peroxidase‐like activity were reported by many groups as well . For examples, Huang et al reported that Fe–Co bimetallic alloy nanoparticles (Fe–Co NPs) possessed highly peroxidase‐like activity and its application for glucose biosensor.…”
Section: Glucose Biosensormentioning
confidence: 99%
“…Peroxidase mimetics have been intensively utilized in the colorimetric assays for various analysts due to their low cost and high stability [31,[38][39][40][41][42][43]. Prussian blue nanoparticles (PB NPs) have also been proven to exhibit intrinsic peroxidase-like activity and they have been successfully used for colorimetric sensing of H 2 O 2 and glucose [44].…”
Section: Introductionmentioning
confidence: 99%
“…The regression equation was y = 2.984 x + 0.073 ( R 2 = 0.998) with the linear range of 0.001–0.3 × 10 −3 m . The limit of detection was 0.6 µM (S/N = 3), which was lower than that of reported two‐step assay and one‐pot enzymatic assay . In addition, the response time (30 min) was shorter than that (more than 7 h) of the reported Au NPs‐based enzyme‐free assay method .…”
Section: Resultsmentioning
confidence: 61%